Charge transport mechanism and memristive effect in a thin film based on fluorinated polyaryl ether containing 1,4-dioxo-thioxanthene-9-one in-chain blocks - Андрей Андреевич Гисматулин; Владимир Алексеевич Пустоваров; Данила Сергеевич Одинцов; Ирина Александровна Оськина; Инна Казимировна Шундрина; Иван Алексеевич Азаров; Леонид Анатольевич Шундрин; Владимир Алексеевич Гриценко (Physics of Complex Systems)
A new fluorinated thermally stable polyaryl ether with electron-withdrawing thioxanthenone in-chain block (FPAE-ThS) was synthesized through the interaction of perfluorobiphenyl with 1,4-dihydroxy-9H-thioxanthene-9-one. The charge transport mechanism within the FPAE-ThS film is governed by the phonon-assisted tunneling between neighbouring traps. The thermal (1.0 eV) and optical trap (2.0 eV) ionization energies, as well as the trap concentration (N = 1.0 × 1020 cm–3), are determined. The value of half Stokes shift (1.1 eV), obtained from the photoluminescence and photoluminescence excitation spectra, is consistent with the results of charge transport simulation. Furthermore, a prototype memory device based on the FPAE-ThS film demonstrates the resistive switching behavior with a four-order difference in the resistance between its low- and high-resistance states.